2009
DOI: 10.1038/onc.2009.341
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein signature may improve detection of ductal carcinoma in situ of the breast

Abstract: Ductal carcinoma in situ (DCIS) of the breast is part of a spectrum of preinvasive lesions that originate within normal breast tissue and progress to invasive breast cancer. The detection of DCIS is important for the reduction of mortality from breast cancer, but the diagnosis of preinvasive breast tumors is hampered by the lack of an adequate detection method. To identify the changes in protein expression during the initial stage of tumorigenesis and to identify the presence of new DCIS markers, we analysed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 61 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…Examples are the increased serum levels of C3a that indicate the presence of colorectal tumors (Habermann et al, 2006), hepatitis C virus-related hepatocellular carcinoma (Lee et al, 2006a;Kanmura et al, 2010), benign prostatic hyperplasia (Xie et al, 2011), and ductal carcinoma in situ of the breast (Solassol et al, 2010). C4a has recently been shown to be elevated in patients with chronic hepatitis C infection and active disease but is even higher in infected but asymptomatic individuals (Imakiire et al, 2012).…”
Section: A Complement Peptides Are Important Biomarkers Of Diseasementioning
confidence: 99%
“…Examples are the increased serum levels of C3a that indicate the presence of colorectal tumors (Habermann et al, 2006), hepatitis C virus-related hepatocellular carcinoma (Lee et al, 2006a;Kanmura et al, 2010), benign prostatic hyperplasia (Xie et al, 2011), and ductal carcinoma in situ of the breast (Solassol et al, 2010). C4a has recently been shown to be elevated in patients with chronic hepatitis C infection and active disease but is even higher in infected but asymptomatic individuals (Imakiire et al, 2012).…”
Section: A Complement Peptides Are Important Biomarkers Of Diseasementioning
confidence: 99%
“…[23] Moreover, there were similar peaks between our results and what reported previously on serum samples (approximate registered m/z values 2,742, 3,992, 5,877, 6,489,8,888,8,931,8,942, and 8,973 Da). [24] Notably, protein peak at 8.9 kDa has been reported in numerous previous studies, [17,18,[20][21][22][23][24][25] indicating its potential values in the diagnosis of breast cancer and the evaluation of treatments and NACT.…”
Section: Discussionmentioning
confidence: 97%
“…[17,18]. Briefly, proteins were extracted from the tumor samples and separated on 16% Tris-glycine sodium dodecyl sulfate-polyacrylamide gels electrophoresis (SDS-PAGE), and subsequently transferred onto polyvinylidene fluoride membranes.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…C3a des-arginine anaphylatoxin Levels of C3a desArg (molecular weight: 8,938 Da) were higher in breast cancer cases compared to healthy controls in six studies [19][20][21][22][23][24], while in two other studies lower levels were found in breast cancer cases [25,26]. These two studies investigated the same group of breast cancer cases and healthy controls [25,26], which was extended with about 100 cases and 80 controls in the most recent study [25].…”
Section: Breast Cancer Biomarkers From Seldiand Maldi-tof Ms Studiesmentioning
confidence: 88%